Play like a man : my life in Poster Children - Marshack, Rose, 1965- (Urbana : University of Illinois Press, 2023)
"As a member of Poster Children, Rose Marshack took part in entwined revolutions. Marshack and other women seized a much-elevated profile in music during the indie rock breakthrough while the advent of new digital technologies transformed the recording and marketing of music. Touring in a van, meeting your idols, juggling a programming job with music, keeping control and credibility, the perils of an independent record label (and the greater perils of a major)-Marshack chronicles the band's day-to-day life and punctuates her account with excerpts from her tour reports and hard-learned lessons on how to rock, program, and teach while female. She also details the ways Poster Children applied punk's DIY ethos to digital tech as a way to connect with fans via then-new media like pkids listservs, internet radio, and enhanced CDs. An inside look at a scene and a career, Play Like a Man is the evocative and humorous tale of one woman's life in the trenches and online"--
Part One. 1980s : College. Origin Story ; The Scene at College ; Punk Bands in Dorms ; Computers ; Play Like a Man -- Part Two. 1987-1992 : Pre-major Label Life. The Indie Code of Ethics ; Local ; Regional ; National -- Part Three. 1993-1996 : Major Label Life ; Mashed Potatoes ; Recording ; Touring ; Radio Sucks ; Computer Experiments ; Expectations ; Big Changes -- Part Four. 1997 : Post Major Label. Online Participation ; Life as a Woman ; How to Look at Things ; Teaching -- Appendix. List of Poster Children Alumni.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on February 20, 2023).
eBooks on EBSCOhost
Keywords: Marshack, Rose, -- 1965-; Poster Children (Musical group); Women bass guitarists -- United States -- Biography; Women alternative rock musicians -- United States -- Biography; Bass guitarists -- United States -- Biography; Alternative rock musicians -- United States -- Biography; Bassistes (Guitare) -- États-Unis -- Biographies; Musiciens de rock alternatif -- États-Unis -- Biographies; MUSIC / Genres & Styles / Punk; BIOGRAPHY & AUTOBIOGRAPHY / Music; Alternative rock musicians; Bass guitarists; Women alternative rock musicians; Women bass guitarists; United States; Biographies